(3GdZeGR Ydi GddeGR aj GdCMGOjK GdVYjaIs - (3LdGd GdOjf GdSeghOj GdTGaYjs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3hHYO ajbhd GdTjN LdGd GdOjf GdSeghOi GdTGaYi deG QCjJ ef dG jNGa jNdW GdCMGOjK GdUMjMI HGdhGgjI s
(3BNQgG (B:s
(3MOjK jhe Uhece jhe fMQce bGd ai GdebGUO Yf LeGYI ef GdMaGX dG CUd dg ai cJH GdMOjK hGddg CYde HGdMOjK JeJ GdQSGdIai GdCMGOjK GdVYjaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO dGSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs